A Survey of RDF Stores & SPARQL Engines for Querying Knowledge Graphs - Ali, Waqas; Saleem, Muhammad; Yao, Bin; Hogan, Aidan; Ngonga Ngomo, Axel-Cyrille (CoRR)

Knowledge Graph Question Answering using Graph-Pattern Isomorphism - Vollmers, Daniel; Jalota, Rricha; Moussallem, Diego; Topiwala, Hardik; Ngonga Ngomo, Axel-Cyrille; Usbeck, Ricardo (CoRR)

MLCheck- Property-Driven Testing of Machine Learning Models - Sharma, Arnab; Demir, Caglar; Ngonga Ngomo, Axel-Cyrille; Wehrheim, Heike (CoRR)

Open Data Portal Germany (OPAL) Projektergebnisse - Wilke, Adrian; Ngonga Ngomo, Axel-Cyrille (CoRR)

Out-of-Vocabulary Entities in Link Prediction - Demir, Caglar; Ngonga Ngomo, Axel-Cyrille (CoRR)

DRILL- Deep Reinforcement Learning for Refinement Operators in ALC - Demir, Caglar; Ngonga Ngomo, Axel-Cyrille (CoRR)

Trust Me, I’m Confident – Are Confident Members of the Crowd Better at Evaluating Business Model Ideas? - Laux, Florian; Görzen, Thomas (Proceedings of the 42nd International Conference on Information Systems (ICIS))

Zinc Anodizing: Structural Diversity of Anodic Zinc Oxide Controlled by the Type of Electrolyte - Engelkemeier, Katja; Sun, Aijia; Voswinkel, Dietrich; Grydin, Olexandr; Schaper, Mirko; Bremser, Wolfgang (ChemElectroChem)

Reinforcement Learning for Admission Control in Wireless Virtual Network Embedding - Afifi, Haitham; Sauer, Fabian Jakob; Karl, Holger (2021 IEEE International Conference on Advanced Networks and Telecommunications Systems (ANTS) (ANTS'21))
Using Service Function Chaining (SFC) in wireless networks became popular in many domains like networking and multimedia. It relies on allocating network resources to incoming SFCs requests, via a Virtual Network Embedding (VNE) algorithm, so that it optimizes the performance of the SFC. When the load of incoming requests -- competing for the limited network resources -- increases, it becomes challenging to decide which requests should be admitted and which one should be rejected. In this work, we propose a deep Reinforcement learning (RL) solution that can learn the admission policy for different dependencies, such as the service lifetime and the priority of incoming requests. We compare the deep RL solution to a first-come-first-serve baseline that admits a request whenever there are available resources. We show that deep RL outperforms the baseline and provides higher acceptance rate with low rejections even when there are enough resources.
Keywords: reinforcement learning; admission control; wireless sensor networks

Reinforcement Learning-based Microphone Selection in Wireless Acoustic Sensor Networks considering Network and Acoustic Utilities - Afifi, Haitham; Guenther, Michael; Brendel, Andreas; Karl, Holger; Kellermann, Walter (14. ITG Conference on Speech Communication (ITG 2021))
Wireless Acoustic Sensor Networks (WASNs) have a wide range of audio signal processing applications. Due to the spatial diversity of the microphone and their relative position to the acoustic source, not all microphones are equally useful for subsequent audio signal processing tasks, nor do they all have the same wireless data transmission rates. Hence, a central task in WASNs is to balance a microphone’s estimated acoustic utility against its transmission delay, selecting a best-possible subset of microphones to record audio signals. In this work, we use reinforcement learning to decide if a microphone should be used or switched off to maximize the acoustic quality at low transmission delays, while minimizing switching frequency. In experiments with moving sources in a simulated acoustic environment, our method outperforms naive baseline comparisons
Keywords: microphone utility; microphone selection; wireless acoustic sensor network; network delay; reinforcement learning

Network-Aware Optimal Microphone Channel Selection in Wireless Acoustic Sensor Networks - Gunther, Michael; Afifi, Haitham; Brendel, Andreas; Karl, Holger; Kellermann, Walter (ICASSP 2021 - 2021 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

ALPACA: Application Layer Protocol Confusion - Analyzing and Mitigating Cracks in TLS Authentication - Brinkmann, Marcus; Dresen, Christian; Merget, Robert; Poddebniak, Damian; Müller, Jens; Somorovsky, Juraj; Schwenk, Jörg; Schinzel, Sebastian (30th USENIX Security Symposium (USENIX Security 21))

Raccoon Attack: Finding and Exploiting Most-Significant-Bit-Oracles in TLS-DH(E) - Merget, Robert; Brinkmann, Marcus; Aviram, Nimrod; Somorovsky, Juraj; Mittmann, Johannes; Schwenk, Jörg (30th USENIX Security Symposium (USENIX Security 21))

Experimental and Numerical Investigations into the Influence of the Process Parameters During the Deep Drawing of Fiber Metal Laminates - Heggemann, Thomas; Sapli, Hüseyin; Homberg, W. (Forming the Future)

Simplified Numerical Calculation of the Isothermal, Three-Dimensional, Non-Newtonian Flow Characteristics of Single-Screw Melt-Extruders - Stüker, Daniel; Schöppner, Volker

Non-Isothermal Calculation of the Pressure-Throughput-Characteristics of Single Screw Melt-Extruders - Stüker, Daniel; Schöppner, Volker

ITiCSE 2021: 26th ACM Conference on Innovation and Technology in Computer Science Education, Virtual Event, Germany, June 26 - July 1, 2021 - Working Group Reports

ITiCSE 2021: 26th ACM Conference on Innovation and Technology in Computer Science Education, Virtual Event, Germany, June 26 - July 1, 2021

Data Science ab Klasse 5 - Konkrete Unterrichtsvorschläge für künstliche Intelligenz unplugged und Datenbewusstsein - Podworny, Susanne; Höper, Lukas; Fleischer, Yannik; Hüsing, Sven; Schulte, Carsten (19. GI-Fachtagung Informatik und Schule, INFOS 2021, Wuppertal, Germany, September 8-10, 2021)

Datenbewusstsein: Aufmerksamkeit für die eigenen Daten - Höper, Lukas; Schulte, Carsten (19. GI-Fachtagung Informatik und Schule, INFOS 2021, Wuppertal, Germany, September 8-10, 2021)

Identity in K-12 Computer Education Research: A Systematic Literature Review - Große-Bölting, Gregor; Gerstenberger, Dietrich Karl-Heinz; Gildehaus, Lara; Mühling, Andreas; Schulte, Carsten (ICER 2021: ACM Conference on International Computing Education Research, Virtual Event, USA, August 16-19, 2021)

ITiCSE 2021 recap - Schulte, Carsten; A. Becker, Brett (ACM SIGCSE Bull.)

Joining of Sheet Metal and Thermoplastic Composites Using Injection Riveting - Moritzer, Elmar; Krassmann, Dimitri; Brikmann, Johannes

Fügen von thermoplastischen Composites mit Metallteilen durch Spritznieten - Moritzer, Elmar; Krassmann, Dimitri; Brikmann, Johannes (Joining Plastics)

Influence of Plasmon Resonances and Symmetry Effects on Second Harmonic Generation in WS2–Plasmonic Hybrid Metasurfaces - Spreyer, Florian; Ruppert, Claudia; Georgi, Philip; Zentgraf, Thomas (ACS Nano)
The nonlinear process of second harmonic generation (SHG) in monolayer (1L) transition metal dichalcogenides (TMD), like WS2, strongly depends on the polarization state of the excitation light. By combination of plasmonic nanostructures with 1L-WS2 by transferring it onto a plasmonic nanoantenna array, a hybrid metasurface is realized impacting the polarization dependency of its SHG. Here, we investigate how plasmonic dipole resonances affect the process of SHG in plasmonic–TMD hybrid metasurfaces by nonlinear spectroscopy. We show that the polarization dependency is affected by the lattice structure of plasmonic nanoantenna arrays as well as by the relative orientation between the 1L-WS2 and the individual plasmonic nanoantennas. In addition, such hybrid metasurfaces show SHG in polarization states, where SHG is usually forbidden for either 1L-WS2 or plasmonic nanoantennas. By comparing the SHG in these channels with the SHG generated by the hybrid metasurface components, we detect an enhancement of the SHG signal by a factor of more than 40. Meanwhile, an attenuation of the SHG signal in usually allowed polarization states is observed. Our study provides valuable insight into hybrid systems where symmetries strongly affect the SHG and enable tailored SHG in 1L-WS2 for future applications.

Learning From Revisions: Quality Assessment of Claims in Argumentation at Scale - Skitalinskaya, Gabriella; Klaff, Jonas; Wachsmuth, Henning (Proceedings of the 16th Conference of the European Chapter of the Association for Computational Linguistics)

Learning Flow Scheduling - Hasnain, Asif; Karl, Holger (2021 IEEE 18th Annual Consumer Communications & Networking Conference (CCNC))
Datacenter applications have different resource requirements from network and developing flow scheduling heuristics for every workload is practically infeasible. In this paper, we show that deep reinforcement learning (RL) can be used to efficiently learn flow scheduling policies for different workloads without manual feature engineering. Specifically, we present LFS, which learns to optimize a high-level performance objective, e.g., maximize the number of flow admissions while meeting the deadlines. The LFS scheduler is trained through deep RL to learn a scheduling policy on continuous online flow arrivals. The evaluation results show that the trained LFS scheduler admits 1.05x more flows than the greedy flow scheduling heuristics under varying network load.
Keywords: Flow scheduling; Deadlines; Reinforcement learning

Extending Business Model Development Tools with Consolidated Expert Knowledge - Gottschalk, Sebastian; Kirchhoff, Jonas; Engels, Gregor (Business Modeling and Software Design)

Dietary Glycaemic Index Labelling: A Global Perspective. - Barclay, AW; LSA, Augustin; Brighenti, F; Delport, E; Henry, CJ; Sievenpiper, JL; Usic, K; Yuexin, Y; Zurbau, A; TMS, Wolever; Astrup, A; Bulló, M; et al. (Nutrients)

Die Gestaltung des Übergangs zur Weiterführenden Schule – Welche Maßnahmen wurden und werden an Grundschulen in NRW praktiziert? - van Ophuysen, Stefanie; Schürer, Sina; Bloh, Bea (Zeitschrift für Grundschulforschung)
Zusammenfassung Studien zum Übergang von der Grund- in die weiterführende Schule gibt es zu zahlreichen Themen. Wie Grundschulen den Übergang zur weiterführenden Schule gestalten, wurde bislang jedoch kaum erforscht. Auf Basis des Forschungsstands werden relevante Maßnahmen identifiziert. In einer online-Befragung an 106 Grundschulen in Nordrhein-Westfalen wurde erfasst, inwiefern diese Maßnahmen tatsächlich umgesetzt werden und als wie relevant bzw. schwierig ihre Umsetzung erachtet wird. Die Ergebnisse werden verglichen mit Daten einer Studie, die 2002 an 71 Grundschulen durchgeführt wurde. Es zeigt sich eine hohe Stabilität der Gestaltung in den letzten 15 Jahren. Maßnahmen, die auf stufenübergreifender Kooperation basieren, werden heute zwar häufiger praktiziert, stehen aber weiterhin am Ende der Rangreihe.

Die Perspektive von Referendar*innen auf Forschendes Lernen - Homt, Martina; Bloh, Bea

Requirements for Processing High-Strength AlZnMgCu Alloys with PBF-LB/M to Achieve Crack-Free and Dense Parts - Heiland, Steffen; Milkereit, Benjamin; Hoyer, Kay-Peter; Zhuravlev, Evgeny; Keßler, Olaf; Schaper, Mirko (Materials)
Processing aluminum alloys employing powder bed fusion of metals (PBF-LB/M) is becoming more attractive for the industry, especially if lightweight applications are needed. Unfortunately, high-strength aluminum alloys such as AA7075 are prone to hot cracking during PBF-LB/M, as well as welding. Both a large solidification range promoted by the alloying elements zinc and copper and a high thermal gradient accompanied with the manufacturing process conditions lead to or favor hot cracking. In the present study, a simple method for modifying the powder surface with titanium carbide nanoparticles (NPs) as a nucleating agent is aimed. The effect on the microstructure with different amounts of the nucleating agent is shown. For the aluminum alloy 7075 with 2.5 ma% titanium carbide nanoparticles, manufactured via PBF-LB/M, crack-free samples with a refined microstructure having no discernible melt pool boundaries and columnar grains are observed. After using a two-step ageing heat treatment, ultimate tensile strengths up to 465 MPa and an 8.9% elongation at break are achieved. Furthermore, it is demonstrated that not all nanoparticles used remain in the melt pool during PBF-LB/M.
Keywords: grain refinement; crack reduction; laser beam melting; aluminum alloy; titanium carbide; nanoparticle; PBF-LB/M

The Strong Scaling Advantage of FPGAs in HPC for N-body Simulations - Menzel, Johannes; Plessl, Christian; Kenter, Tobias (ACM Transactions on Reconfigurable Technology and Systems)
N-body methods are one of the essential algorithmic building blocks of high-performance and parallel computing. Previous research has shown promising performance for implementing n-body simulations with pairwise force calculations on FPGAs. However, to avoid challenges with accumulation and memory access patterns, the presented designs calculate each pair of forces twice, along with both force sums of the involved particles. Also, they require large problem instances with hundreds of thousands of particles to reach their respective peak performance, limiting the applicability for strong scaling scenarios. This work addresses both issues by presenting a novel FPGA design that uses each calculated force twice and overlaps data transfers and computations in a way that allows to reach peak performance even for small problem instances, outperforming previous single precision results even in double precision, and scaling linearly over multiple interconnected FPGAs. For a comparison across architectures, we provide an equally optimized CPU reference, which for large problems actually achieves higher peak performance per device, however, given the strong scaling advantages of the FPGA design, in parallel setups with few thousand particles per device, the FPGA platform achieves highest performance and power efficiency.

Numerical and Experimental Investigation of Zero-Gravity Distillation Units - Wende, Marc; Fischer, Florian; Kenig, Eugeny (Chemical Engineering Transactions)

General relationship between salt concentration and x-ray absorption for binary electrolytes - Steinrück, Hans-Georg (AIP Advances)

Arbeitsbuch Judith Kuckart. Erzählen – Theater – Tanz
In diesem Arbeitsbuch werden die Wege der 1959 in Westfalen geborenen und heute v.a. in Berlin lebenden Judith Kuckart zurückverfolgt – und zwar in den Gattungen Prosa, Theater, Hör-Feature und Film sowie im Bereich Tanz: In all diesen Gattungen hat die Künstlerin seit den 1980er Jahren ein umfassendes OEuvre entwickelt. Im vorliegenden Band werden erstmals alle ihre Schaffensbereiche thematisiert und in ihren Zusammenhängen betrachtet. Dies geschieht mittels wissenschaftlicher Essays, künstlerischer und persönlicher Kurzbeiträge sowie ausführlicher Gespräche mit Judith Kuckart. Ihr künstlerisches Leben und Werk wird auf diese Weise in seinen vielfältigen Aspekten erfasst und der wissenschaftlichen und kulturellen Öffentlichkeit präsentiert.
Keywords: Erzählverfahren deutschsprachige Gegenwartsliteratur Tanztheater Westfalen Heimat Hörspiel

Digitale Räume geben und nehmen: Unterrichtsinteraktion in DSH-Kursen während der COVID-19-Pandemie - Drumm, Sandra; Müller, Mareike; Stenzel, Nadja (Informationen Deutsch als Fremdsprache)
Das Auftreten der COVID-19-Pandemie stellt Fremdsprachenkurse vielerorts vor Herausforderungen. Unter Zuhilfenahme diverser digitaler Tools werden nicht nur Lernmaterialien online geteilt, sondern auch die Interaktion zwischen Lehrenden und Lernenden sowie der Lernenden untereinander in den virtuellen Raum verlagert. Qualitative Interviews mit den Beteiligten erfassen, wie diese mit den Herausforderungen videogestützten Sprachunterrichts umgehen und welche Strategien sie wählen, um Sprachenlernen zu ermöglichen. Die Ergebnisse zeigen auf, wo seitens der Kursorganisation und -durchführung Handlungsbedarf besteht. ----- The rise of the COVID-19 pandemic challenges the teaching and learning of foreign languages at many institutions. The implementation of various digital tools aids not only the online sharing of learning materials, but also shifts teacher-learner and learner-learner interaction to the virtual space. Via qualitative interviews, this study examines how both teachers and learners handle the challenges of language instruction based on videoconferences, and what strategies they employ to enable language learning. The results highlight areas in need of improvement in terms of course organization and facilitation.
Keywords: German language courses at university; interaction; digital space; language learning/teaching via videoconference

MLCHECK–Property-Driven Testing of Machine Learning Classifiers - Sharma, Arnab; Demir, Caglar; Ngonga Ngomo, Axel-Cyrille; Wehrheim, Heike (Proceedings of the 20th IEEE International Conference on Machine Learning and Applications (ICMLA))
In recent years, we observe an increasing amount of software with machine learning components being deployed. This poses the question of quality assurance for such components: how can we validate whether specified requirements are fulfilled by a machine learned software? Current testing and verification approaches either focus on a single requirement (e.g., fairness) or specialize on a single type of machine learning model (e.g., neural networks). In this paper, we propose property-driven testing of machine learning models. Our approach MLCheck encompasses (1) a language for property specification, and (2) a technique for systematic test case generation. The specification language is comparable to property-based testing languages. Test case generation employs advanced verification technology for a systematic, property dependent construction of test suites, without additional user supplied generator functions. We evaluate MLCheck using requirements and data sets from three different application areas (software discrimination, learning on knowledge graphs and security). Our evaluation shows that despite its generality MLCheck can even outperform specialised testing approaches while having a comparable runtime

Systematik zum Einstieg in die Plattformökonomie - Drewel, Marvin

Systematik zur Planung des organisationalen Wandels zum Smart Service-Anbieter - Frank, Maximilian

Rahmenwerk zur Planung und Einführung von Systems Engineering und Model-Based Systems Engineering - Bretz, Lukas

Die Anbahnung einer forschenden Grundhaltung im Verlauf des Praxissemesters: Entwicklungsverläufe und Gelingensbedingungen - Homt, Martina; van Ophuysen, Stefanie

Elternsorgen und Kindersorgen während der Corona-Pandemie - Sander, Andreas; van Ophuysen, Stefanie; Schäfer, Laura; Homt, Martina

Forming Simulation of Tailored Press Hardened Parts - Triebus, Marcel; Reitz, Alexander; Grydin, Olexandr; Grenz, Julian; Schneidt, Andreas; Erhardt, Rüdiger; Tröster, Thomas; Schaper, Mirko (13th European LS-DYNA Conference 2021)

Steigerung der Prognosegüte mechanischer Fügeprozesssimulationen durch den Einsatz einer fügespezifischen Reibmodellierung basierend auf einer experimentellen Parametrisierung - Rossel, Moritz Sebastian; Meschut, Gerson (11. Fügetechnisches Gemeinschaftskolloquium)

Motivationsregulationsformen zum Erwerb pädagogisch-psychologischer Theorien und Befunde im Lehramtsstudium - Grosser, Christine; Wehde, Janis

Die Reflexion der eigenen Lehrtätigkeit von Studierenden in Praxisphasen durch Forschendes Lernen: Prädiktiver Einfluss subjektiver Normen im schulischen und universitären Kontext - Wehde, Janis; Bloh, Bea

Fiber response to pin penetration in dry woven fabric using numerical analysis - Droß, M.; Heyser, Per; Meschut, Gerson; Hürkamp, A.; Dröder, K. (Journal of Advanced Joining Processes)

Großserientaugliche induktive Platinenerwärmung für den Warmformprozess - Tröster, Thomas; Pfeifer, Florian; Nacke, Bernard; Dietrich, André

Kollektive Reflexionsphasen - Bloh, Thiemo

IT-Systeme für das Krisenmanagement - Pottebaum, Jens; Schäfer, Christina (Sicherheitskritische Mensch-Computer-Interaktion)

Die Zukunft sicherheitskritischer Mensch-Computer-Interaktion - Reuter, Christian; Aal, Konstantin; Beham, Frank; Boden, Alexander; Brauner, Florian; Fiedrich, Frank; Fuchs-Kittowski, Frank; Geisler, Stefan; Gennen, Klaus; Herrmann, Dominik; Kaufhold, Marc-André; Klafft, Michael; et al. (Sicherheitskritische Mensch-Computer-Interaktion)

Supporting Innovation Management for SMEs: A Tool for Idea Selection - Gräßler, Iris; Koch, Anna-Sophie; Thiele, Henrik; Dattner, Michael (Proceedings of the ISPIM Innovation Conference)
In innovation management, usually there is a large number of product ideas, not all of which meet the requirements of a company and make sense to pursue further. For selecting the most promising ideas, several methods exist which each focus on a certain aspect. Due to the characteristics of Small and Medium Enterprises (SMEs) such as limited resources, these enterprises have special requirements on methods for selecting ideas. In this study, criteria of SMEs for idea selection are deducted from SME-characteristics. Methods for idea selection are tested for fulfillment of these criteria and the results are combined in a matrix. Together with a guideline, a tool for idea selection in innovation management of SMEs is developed. The results are validated in the context of innovation management in SMEs. By selecting a method, a SME is enabled to make economically viable decisions for their product portfolio, thus ensuring sustainable economic success.
Keywords: innovation management; SME; evaluation method; idea selection; meta-study; idea evaluation

Produktspezifische Optimierung der Nachhaltigkeit im Ersatzteilmanagement. Ganzheitliche Vorgehensweise zur Bewertung der Nachhaltigkeit additiv gefertigter Komponenten für den Aftermarket - Gräßler, Iris; Hillebrand, Stefan; Thiele, Henrik (Digitalisierung im Kontext von Nachhaltigkeit und Klimawandel)
Um der ansteigenden Erderwärmung entgegenzuwirken, erheben immer mehr Regierungen Steuern und Strafzahlungen auf den CO2-Ausstoß. Dieses betrifft auch die Ersatzteil¬versorgung im Automobilbereich. Dabei muss bislang dem Bedarf vorgelagert produziert werden, was mit hohen Lagerkapazitäten und logistischen Aufwänden verbunden ist. CO2-Einsparungen sind daher durch einen Wechsel auf die additive on-demand-Fertigung über ein dezentrales Fertigungsnetzwerk aus Lohndienstleistern möglich. Allerdings ist die dezentrale Ersatzteilfertigung trotz Einbezug des CO2-Preises nicht in jedem Fall wirtschaftlich. Der Grund hierfür liegt in der Abhängigkeit der Gesamtkosten von Faktoren wie Bauteilgeometrie, Logistikaufwand und Stückzahl. Im vorliegenden Beitrag wird eine Vorgehensweise für den Vergleich einer zentralen mit einer dezentralen Ersatzteilversorgung durch die Ergänzung relevanter, produktspezifischer Kennwerte für die additive Bauteilfertigung beschrieben. Neben der Ökobilanz berücksichtigt die entwickelte Methode die wirtschaftliche Rentabilität des Herstellungsverfahrens. Die Validierung dieser Vorgehensweise erfolgt in Kooperation mit einem deutschen Automobilhersteller. Die entwickelte Vorgehensweise dient Automobilherstellern als Entscheidungsunterstützung bei der Fragestellung, ob einzelne Ersatzteilkomponenten herkömmlich oder additiv gefertigt werden.

Should I stay or should I go? The dark side of corporate entrepreneurship - Tomin, Slawa; Krebs, Benjamin (Frontiers of Entrepreneurship Research)

HRM in the Germanic context - Krebs, Benjamin; Wach, Bernhard Alexander; Wehner, Marius Claus; Reichel, Astrid; Mayrhofer, Wolfgang; Sender, Anna; Staffelbach, Bruno; Ligthart, Paul (Handbook on contextual approaches to human resource management)

Aus der Forschung in die Anwendung - Materialqualifizierung im Kunststoff Freiformen - Moritzer, Elmar; Hecker, Felix; Hirsch, André (Kunststoffland NRW report)

Fluid Dynamics of the Open Port Interface for High-Speed Nanoliter Volume Sampling Mass Spectrometry - Liu, Chang; Van Berkel, Gary J.; Kovarik, Peter; Perot, J. Blair; Inguva, Venkatesh; Covey, Thomas R. (Analytical Chemistry)

Analyzing Approximate Value Iteration Algorithms - Ramaswamy, Arunselvan; Bhatnagar, Shalabh (Mathematics of Operations Research (to appear))

Automated Detection of Side Channels in Cryptographic Protocols: DROWN the ROBOTs! - Drees, Jan Peter; Gupta, Pritha; Hüllermeier, Eyke; Jager, Tibor; Konze, Alexander; Priesterjahn, Claudia; Ramaswamy, Arunselvan; Somorovsky, Juraj (14th ACM Workshop on Artificial Intelligence and Security)

Deep Q-Learning: Theoretical Insights from an Asymptotic Analysis - Ramaswamy, Arunselvan; Hüllermeier, Eyke (IEEE Transactions on Artificial Intelligence (to appear))

Weiterentwicklung von GITBlow für dünnwandige Hohlstrukturen auf Organoblechen - Moritzer, Elmar; Kröker, Michael (CU reports)

Simulative analysis of the filling process in the 2K GITBlow process on organo sheets - Moritzer, Elmar; Kröker, Michael

Validation of an Online State Estimation Concept for Microscopic Traffic Simulations◆ - Malena, Kevin; Link, Christopher; Mertin, Sven; Gausemeier, Sandra; Trächtler, Ansgar (2021 IEEE Transportation Electrification Conference & Expo (ITEC))
This paper deals with a novel method for the online fitting of a microscopic traffic simulation model to the current state of a real world traffic area. The traffic state estimation is based on limited data of different measurement sources and guarantees general accordance of reality and simulation in terms of multimodal road traffic counts and vehicle speeds. The research is embedded in the challenge of improving the traffic by controlling the traffic light systems (TLS) of the examined area. Therefore, the current traffic state and the predicted route choices of individual road users are the matter of interest. The concept is generally transferable to any road traffic system. To give an impression of the accuracy and potential of the approach, the validation and first application results are presented.

Einfluss eines beheizten Bauraums auf die Schweißnahtqualität - Moritzer, Elmar; Wächter, Julian (Plastverarbeiter)

Tensor-based computation of metastable and coherent sets - Nüske, Feliks; Gelß, Patrick; Klus, Stefan; Clementi, Cecilia (Physica D: Nonlinear Phenomena)

Symmetric and antisymmetric kernels for machine learning problems in quantum physics and chemistry - Klus, Stefan; Gelß, Patrick; Nüske, Feliks; Noé, Frank (Machine Learning: Science and Technology)

Pulverherstellung und Verrundung neuer Polymermaterialien für das selektive Lasersintern (SLS) - Poster - Ponusamy, SathishKumar

A model for the carbon fiber breakage along the twin‐screw extruder - Malatyali, Hatice; Schöppner, Volker; Rabeneck, Nils; Hanselle, Felix; Austermeier, Laura; Karch, David (SPE Polymers)

The Influence of Process Conditions on the Fiber Length Reduction for Recycled Carbon Fibers - Malatyali, Hatice; Schöppner, Volker; Lochbaum, Ella; Bomm, Igor; Hanselle, Felix (SPE ANTEC)

Reproducibility analysis of fiber length measurements during processing with twin screw extruders - Malatyali, Hatice; Schöppner, Volker; Akar, Seyit Ali; Hanselle, Felix; Austermeier, Laura (SPE ANTEC)

The Hare and the Hedgehog: Empirical evidence on the relationship between the individual Pace of Life and the speed-accuracy continuum - Hoffmann, Christin; Hoppe, Julia Amelie; Ziemann, Niklas (PloS one)

The relationship between talent management and individual and organizational performance - Krebs, Benjamin; Wehner, Marius Claus (The Routledge companion to talent management)

Lebensdauer vorhersagen? - Gevers, Karina; Schöppner, Volker (K-Zeitung)
Keywords: Infrarotschweißen; Glasfaserverstärkte Kunststoffe; Lebensdauer; Langzeitbelastung

Heated tool butt welding of two different materials – Established methods versus artificial intelligence - Gevers, Karina; Schöppner, Volker; Hüllermeier, Eyke

Development of scale up rules for quasi-simultaneous laser transmission welding of thermoplastics - Arndt, Theresa; Schöppner, Volker

Design and Experimental Investigation of an Additively Manufactured PMSM Rotor - Urbanek, Stefan; Pauline, Frey; Magerkohl, Sebastian; Zimmer, Detmar; Tasche, Lennart; Schaper, Mirko; Ponick, Bernd
Keywords: Elektromotor; Elektromaschine; Additive Fertigung; AF; AM; Additive Manufacturing; DMRC; KAt

3D-Druck in der industriellen Anwendung - Funktions- und fertigungsgerechte Konstruktion mit additiver Fertigung (Vortrag) - Magerkohl, Sebastian; Brüggemann, Jan-Peter

DEVELOPMENT OF A NEW METHOD TO EVALUATE THE DISTRIBUTIVE MIXING QUALITY BASED ON THE PARTICLE TRACKING METHOD AND THE DELAUNAY TRIANGULATION - Frank, Maximilian; Schöppner, Volker (ANTEC® 2021)

Influence of angled dispersion gas on coaxial atomization, spray and flame formation in the context of spray-flame synthesis of nanoparticles - Bieber, M.; Al-Khatib, M.; Fröde, F.; Pitsch, H.; Reddemann, M. A.; Schmid, H-J.; Tischendorf, R.; Kneer, R. (Experiments in Fluids)
Liquid atomization determines the initial conditions for flame formation and particle synthesis. Without a stable flame, high droplet velocities and thus short droplet residence time in the flame may lead to droplets being injected into an extinguished flame, which influences synthesis and final particle output. An experimental investigation of spray formation and flame stability is performed through high-speed visualization. Targeted variation of nozzle geometry is applied to improve spray-flame interaction and compared to a standardized burner. Timescales of spray density and flame fluctuations are quantified and compared, where the latter were significantly larger and hence not correlated. Instead, dispersion gas forms a barrier between spray phase and pilot flame; hence, ignition depends on large liquid lumps with high radial momentum to break through the dispersion gas for spray ignition. Angling of dispersion gas flow increases radial shear and turbulence and leads to refined atomization and improved flame stability. To investigate the nozzle influence on particle formation, particle characteristics are examined by online and offline analytics with focus on particle structures and product purity. The modified nozzle produced smaller primary particle sizes, thus indicating a sensitivity of sintering dominance on the nozzle geometry. Impurities impact the examination of particle structures and general particle functionality. Carbon contamination was apparent in synthesized particles and also indicated sensitivity to nozzle geometry. Discrepancies to literature data are discussed regarding differences in flame activity and droplet characteristics. The report highlights, how product characteristics can differ crucially due to changes in nozzle geometry despite comparable operating conditions.

Separation of Multi-Component Parts for Mechanical Recycling – An Approach to Produce Hard-Soft Combinations with a Better Recyclability - Hopp, Matthias; Mühlhoff, Frederik Marvin (79th Annual Technical Conference of the Society of Plastics Engineers (ANTEC))

Transitioning to Condition-Based Maintenance on the Distribution Grid: Deriving Design Principles from a Qualitative Study - zur Heiden, Philipp; Priefer, Jennifer (Pre-Conference 16th International Congress on Wirtschaftsinformatik at Universität Duisburg-Essen)

Constructions of a National Threat: Contextualising the Rhetorical Management of the COVID-19 Pandemic in Britain - Tönnies, Merle (Mentalities and Materialities: Essays in Honour of Jürgen Kamm)

Faster, harder, greener? Empirical evidence on the role of the individual Pace of Life for productivity and pro-environmental behavior - Hoffmann, Christin; Hoppe, Julia Amelie; Ziemann, Niklas (Ecological Economics)

Kleine Tropfen, große Wirkung - Moritzer, Elmar; Hecker, Felix; Hirsch, André (Kunststoffe)

Assessment of AlZnMgCu alloy powder modification for crack-free laser powder bed fusion by differential fast scanning calorimetry - Zhuravlev, Evgeny; Milkereit, Benjamin; Yang, Bin; Heiland, Steffen; Vieth, Pascal; Voigt, Markus; Schaper, Mirko; Grundmeier, Guido; Schick, Christoph; Kessler, Olaf (Materials & Design)
Additive manufacturing, e.g. by laser powder bed fusion (LPBF), is very attractive for lightweight constructions, as complex and stress-optimised structures integrating multiple functions can be produced within one process. Unfortunately, high strength AlZnMgCu alloys tend to hot cracking during LPBF and thus have not so far been applicable. In this work the melting and solidification behaviour of AlZnMgCu alloy powder variants with particle surface inoculation was analysed by Differential Fast Scanning Calorimetry. The aim is to establish a method that makes it possible to assess powder modifications in terms of their suitability for LPBF on a laboratory scale requiring only small amounts of powder. Therefore, solidification undercooling is evaluated at cooling rates relevant for LPBF. A method for the temperature correction and normalisation of the DFSC results is proposed. Two ways of powder modification were tested for the powder particles surface inoculation by titanium carbide (TiC) nanoparticles: via wet-chemical deposition and via mechanical mixing. A low undercooling from DFSC correlates with a low number of cracks of LPBF-manufactured cubes. It appears that a reduced undercooling combined with reduced solidification onset scatter indicates the possibility of crack-free LPBF of alloys that otherwise tend to hot cracking.
Keywords: Aluminium alloy 7075; Differential fast scanning calorimetry; Solidification; Undercooling; Additive manufacturing

I-AID: Identifying Actionable Information From Disaster-Related Tweets - M. Zahera, Hamada; Jalota, Rricha; Ahmed Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (IEEE Access)

Knowledge Graphs - Hogan, Aidan; Blomqvist, Eva; Cochez, Michael; d'Amato, Claudia; de Melo, Gerard; Gutiérrez, Claudio; Kirrane, Sabrina; Emilio Labra Gayo, José; Navigli, Roberto; Neumaier, Sebastian; Ngonga Ngomo, Axel-Cyrille; Polleres, Axel; et al. (ACM Comput. Surv.)

Attention to diversity in German CLIL classrooms: Multi-perspective research on students’ and teachers’ perceptions - Siepmann, Philipp; Rumlich, Dominik; Matz, Frauke; Römhild, Ricardo (International Journal of Bilingual Education and Bilingualism)

Bilingualer Unterricht. Aktuelle Herausforderungen und neue Chancen (Fremdsprachen Lehren und Lernen)

Freies Format 2: Nachwuchs-Café (reloaded): Auf dem Weg zur Professur... - Rumlich, Dominik; Matz, Frauke; Juchem-Grundmann, Constanze (Sprache, Kulturen, Identitäten : Umbrüche durch Digitalisierung: 28. Kongress der Deutschen Gesellschaft für Fremdsprachenforschung. Würzburg, 25.-28. September 2019)

Self-Assembled Fibrinogen Hydro- and Aerogels with Fibrin-like 3D Structures - Hense, Dominik; Büngeler, Anne; Kollmann, Fabian; Hanke, Marcel; Orive, Alejandro; Keller, Adrian; Grundmeier, Guido; Huber, Klaus; Strube, Oliver I. (Biomacromolecules)

Exploring intensity-dependent modulations in EEG resting-state network efficiency induced by exercise - Büchel, Daniel; Sandbakk, Øyvind; Baumeister, Jochen (European Journal of Applied Physiology)
Abstract Purpose Exhaustive cardiovascular load can affect neural processing and is associated with decreases in sensorimotor performance. The purpose of this study was to explore intensity-dependent modulations in brain network efficiency in response to treadmill running assessed from resting-state electroencephalography (EEG) measures. Methods Sixteen trained participants were tested for individual peak oxygen uptake (VO 2 peak ) and performed an incremental treadmill exercise at 50% (10 min), 70% (10 min) and 90% speed VO 2 peak (all-out) followed by cool-down running and active recovery. Before the experiment and after each stage, borg scale (BS), blood lactate concentration (B La ), resting heartrate (HR rest ) and 64-channel EEG resting state were assessed. To analyze network efficiency, graph theory was applied to derive small world index (SWI) from EEG data in theta, alpha-1 and alpha-2 frequency bands. Results Analysis of variance for repeated measures revealed significant main effects for intensity on BS, B La , HR rest and SWI. While BS, B La and HR rest indicated maxima after all-out, SWI showed a reduction in the theta network after all-out. Conclusion Our explorative approach suggests intensity-dependent modulations of resting-state brain networks, since exhaustive exercise temporarily reduces brain network efficiency. Resting-state network assessment may prospectively play a role in training monitoring by displaying the readiness and efficiency of the central nervous system in different training situations.

Stance leg and surface stability modulate cortical activity during human single leg stance - Büchel, Daniel; Lehmann, Tim; Ullrich, Sarah; Cockcroft, John; Louw, Quinette; Baumeister, Jochen (Experimental Brain Research)
Abstract Mobile Electroencephalography (EEG) provides insights into cortical contributions to postural control. Although changes in theta (4–8 Hz) and alpha frequency power (8–12 Hz) were shown to reflect attentional and sensorimotor processing during balance tasks, information about the effect of stance leg on cortical processing related to postural control is lacking. Therefore, the aim was to examine patterns of cortical activity during single-leg stance with varying surface stability. EEG and force plate data from 21 healthy males (22.43 ± 2.23 years) was recorded during unipedal stance (left/right) on a stable and unstable surface. Using source-space analysis, power spectral density was analyzed in the theta, alpha-1 (8–10 Hz) and alpha-2 (10–12 Hz) frequency bands. Repeated measures ANOVA with the factors leg and surface stability revealed significant interaction effects in the left ( p = 0.045, η p 2 = 0.13) and right motor clusters ( F = 16.156; p = 0.001, η p 2 = 0.41). Furthermore, significant main effects for surface stability were observed for the fronto-central cluster (theta), left and right motor (alpha-1), as well as for the right parieto-occipital cluster (alpha-1/alpha-2). Leg dependent changes in alpha-2 power may indicate lateralized patterns of cortical processing in motor areas during single-leg stance. Future studies may therefore consider lateralized patterns of cortical activity for the interpretation of postural deficiencies in unilateral lower limb injuries.

Functional Cortical Connectivity Related to Postural Control in Patients Six Weeks After Anterior Cruciate Ligament Reconstruction - Lehmann, Tim; Büchel, Daniel; Mouton, Caroline; Gokeler, Alli; Seil, Romain; Baumeister, Jochen (Frontiers in Human Neuroscience)
Whereas initial findings have already identified cortical patterns accompanying proprioceptive deficiencies in patients after anterior cruciate ligament reconstruction (ACLR), little is known about compensatory sensorimotor mechanisms for re-establishing postural control. Therefore, the aim of the present study was to explore leg dependent patterns of cortical contributions to postural control in patients 6 weeks following ACLR. A total of 12 patients after ACLR (25.1 ± 3.2 years, 178.1 ± 9.7 cm, 77.5 ± 14.4 kg) and another 12 gender, age, and activity matched healthy controls participated in this study. All subjects performed 10 × 30 s. single leg stances on each leg, equipped with 64-channel mobile electroencephalography (EEG). Postural stability was quantified by area of sway and sway velocity. Estimations of the weighted phase lag index were conducted as a cortical measure of functional connectivity. The findings showed significant group × leg interactions for increased functional connectivity in the anterior cruciate ligament (ACL) injured leg, predominantly including fronto−parietal [ F (1, 22) = 8.41, p ≤ 0.008, η 2 = 0.28], fronto−occipital [ F (1, 22) = 4.43, p ≤ 0.047, η 2 = 0.17], parieto−motor [ F (1, 22) = 10.30, p ≤ 0.004, η 2 = 0.32], occipito−motor [ F (1, 22) = 5.21, p ≤ 0.032, η 2 = 0.19], and occipito−parietal [ F (1, 22) = 4.60, p ≤ 0.043, η 2 = 0.17] intra−hemispherical connections in the contralateral hemisphere and occipito−motor [ F (1, 22) = 7.33, p ≤ 0.013, η 2 = 0.25] on the ipsilateral hemisphere to the injured leg. Higher functional connectivity in patients after ACLR, attained by increased emphasis of functional connections incorporating the somatosensory and visual areas, may serve as a compensatory mechanism to control postural stability of the injured leg in the early phase of rehabilitation. These preliminary results may help to develop new neurophysiological assessments for detecting functional deficiencies after ACLR in the future.

Beratung bei Studienzweifel als Instrument des Qualitätsmanagements von Studium und Lehre - Sloane, Hannah; Mauer, Eileen (Ursprünge hinterfragen - Vielfalt ergründen - Praxis einordnen)

Quantifying the coupling strength of adhesively bonded materials by investigating mode repulsion regions - Zeipert, Henning; Johannesmann, Sarah; Nicolai, Marcel; Lugovtsova, Yevgeniya; Prager, Jens; Henning, Bernd (Fortschritte der Akustik - DAGA 2021)

Ansätze zur Diagnose und Förderung von Problemlösefähigkeiten in der Studieneingangsphase Physik - Lahme, Simon; Bauer, Anna; Reinhold, Peter (Phydid B, Didaktik der Physik, Beiträge zur DPG-Frühjahrstagung)

IN OTHER WORDS: A NAIVE APPROACH TO TEXT SPINNING - Bäumer, Frederik Simon; Kersting, Joschka; Denisov, Sergej; Geierhos, Michaela (PROCEEDINGS OF THE INTERNATIONAL CONFERENCES ON WWW/INTERNET 2021 AND APPLIED COMPUTING 2021)
Content is the new oil. Users consume billions of terabytes a day while surfing on news sites or blogs, posting on social media sites, and sending chat messages around the globe. While content is heterogeneous, the dominant form of web content is text. There are situations where more diversity needs to be introduced into text content, for example, to reuse it on websites or to allow a chatbot to base its models on the information conveyed rather than of the language used. In order to achieve this, paraphrasing techniques have been developed: One example is Text spinning, a technique that automatically paraphrases text while leaving the intent intact. This makes it easier to reuse content, or to change the language generated by the bot more human. One method for modifying texts is a combination of translation and back-translation. This paper presents NATTS, a naive approach that uses transformer-based translation models to create diversified text, combining translation steps in one model. An advantage of this approach is that it can be fine-tuned and handle technical language.
Keywords: Software Requirements; Natural Language Processing; Transfer Learning; On-The-Fly Computing

Szenario-Technik mit digitalen Technologien (in Druck) - Ködding, Patrick; Dumitrescu, Roman (Digitalisierung souverän gestalten)